PROSES ALIGNMENT PADA SHAFT TURBIN UNIT 2 PLTA TES - Gultom, Hendriadi Pargaulan; Suryono, Ahmad Fauzan (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2021)
TES Hydroelectric Power Plant is engaged in power generation. In the process of generating electricity, hydro power relies on a turbine unit that can convert the potential and kinetic energy of water into electrical energy. In the process of the turbine producing electrical energy there are many obstacles that occur which result in a reduction in the productivity of the turbine work, one of the causes is misalignment of the shaft. Misalignment on the shaft can be overcome by carrying out an alignment process which aims to make the shaft return to its initial position so that it is parallel to the other shaft. The alignment process is carried out to get the axial and radial values on the shaft which is then carried out by the adjusting process. The adjusting process is carried out so that the position of the shaft that is out of tolerance returns to the tolerance position and the work of the turbine can return to normal.